1-[4-(4-Nitrophenyl)piperazin-1-yl]-2-(4,5,6,7-tetrahydrothieno[3,2-c]pyridin-5-yl)ethanone - Mu, Shuai (International Union of Crystallography, 2010)
The title compound, C(19)H(22)N(4)O(3)S, comprises a thienopyridine moiety which is characteristic for antiplatelet agents of the clopidogrel class of compounds. In the crystal, inversion dimers are formed through pairs of C—H⋯O interactions. The benzene ring plane and the nitro plane are almost coplanar, with a dihedral angle of 0.83 (2)°. The piperazine ring adopts a chair conformation.